1997
DOI: 10.1117/12.271065
|View full text |Cite
|
Sign up to set email alerts
|

<title>Current spreading in apertured vertical-cavity lasers</title>

Abstract: Scaling of the threshold current density in apertured vertical cavity lasers is limited by scattering losses, current spreading, and carrier diffusion. We consider the contributions of all three effects, but focus on current spreading. We analyze a vertical cavity laser (VCL) with low scattering losses so the scaling of the threshold current density is dominated by current spreading under the aperture. We show that a simple analytic estimate (appropriate for circular geometry) for the increase in threshold mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…We see no strong variation with size which suggests that additional carriers injected above threshold going into unclamped regions relative to clamped regions changes negligibly with size. There are a number of assumptions which keep us from unequivocally concluding the lateral injection efficiency is not changing with size, but these data provide strong evidence that there is little variation laterally, which is in agreement with theoretical predictions [8]. Lastly, we should note that these measurements are on devices with low scattering losses.…”
Section: Appendix Scaling Of the Clamping Efficiencysupporting
confidence: 76%
See 3 more Smart Citations
“…We see no strong variation with size which suggests that additional carriers injected above threshold going into unclamped regions relative to clamped regions changes negligibly with size. There are a number of assumptions which keep us from unequivocally concluding the lateral injection efficiency is not changing with size, but these data provide strong evidence that there is little variation laterally, which is in agreement with theoretical predictions [8]. Lastly, we should note that these measurements are on devices with low scattering losses.…”
Section: Appendix Scaling Of the Clamping Efficiencysupporting
confidence: 76%
“…Previous studies have indicated that lateral current spreading between the aperture and the active region can be significant in apertured devices [4], [8], [10]. In Fig.…”
Section: Current Confinementmentioning
confidence: 90%
See 2 more Smart Citations
“…The expansion coefficients a α j and b α j for each region are found by back substitution through (40) and (36).…”
Section: T M Pmentioning
confidence: 99%